Host sanctions and the legume-rhizobium mutualism. - Kiers, E; Rousseau, R; West, SA; Denison, R (2003)
Explaining mutualistic cooperation between species remains one of the greatest problems for evolutionary biology. Why do symbionts provide costly services to a host, indirectly benefiting competitors sharing the same individual host? Host monitoring of symbiont performance and the imposition of sanctions on 'cheats' could stabilize mutualism. Here we show that soybeans penalize rhizobia that fail to fix N(2) inside their root nodules. We prevented a normally mutualistic rhizobium strain from cooperating (fixing N(2)) by replacing air with an N(2)-free atmosphere (Ar:O(2)). A series of experiments at three spatial scales (whole plants, half root systems and individual nodules) demonstrated that forcing non-cooperation (analogous to cheating) decreased the reproductive success of rhizobia by about 50%. Non-invasive monitoring implicated decreased O(2) supply as a possible mechanism for sanctions against cheating rhizobia. More generally, such sanctions by one or both partners may be important in stabilizing a wide range of mutualistic symbioses.